Building Character Together: The Synergistic Role of Parents and Communities in Shaping School Values - Djazilan, Sukron; Wuri Wuryandani (Universitas Nahdlatul Ulama Surabaya, 2024)
Character education is a pivotal element in fostering moral and ethical values among students. This study explores the synergistic impact of parental and community involvement in character education within schools. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participant observations, and document analysis across three schools in diverse socio-economic settings. The findings reveal that parental involvement, such as reinforcing values at home and participating in school activities, significantly enhances students' moral development. Likewise, community engagement through mentorship, resources, and local partnerships provides a supportive environment for instilling positive character traits. However, challenges such as conflicting values, limited time, and communication gaps were identified as barriers to effective collaboration. This research underscores the importance of an integrated approach, aligning efforts between parents, community members, and educators to optimize character education outcomes. The study highlights practical strategies and theoretical contributions, advocating for enhanced communication and joint initiatives to nurture students' character development.